Syphilis among HIV serodiscordant partners associated with Human Papillomavirus Infection in a bisexual man - Boldrini, Neide Aparecida Tosato; Tapias, Bianca Nunes Balmas; Caldas, João Victor Jacomele; Almeida, Susana Lamara Pedras; Ferreira, Dennis de Carvalho; Silva, Alexandre Marques Paes da; Santos, Maria Carmen Lopes Ferreira Silva; Reis, Helena Lucia Barroso dos (Brazilian Journal of Sexually Transmitted Diseases, 2020)
Introduction: Syphilis and HIV infections are sexually transmitted infections whose diagnosis and treatment contribute toward preventing congenital transmission. Objective: To report a case of three sexually transmitted infections detected in a male partner during Couple Consultation and syphilis in the female partner during prenatal care. Case report: A 34-year-old black female G2P1 pregnant woman was referred to an outpatient clinic of sexually transmitted infections in Vitória, Brazil, reporting a 30-day evolution of painless papular lesions in the external genitalia, suggestive of condylomata lata. Nontreponemal tests were positive for syphilis and negative for HIV. The husband reported unprotected receptive anal intercourse and possessed anal condylomatous lesions and perianal condylomata lata. He was positive for both HIV and syphilis. Histopathological findings showed low-grade HPV lesions and the PCR test found 16, 39, and 53 HPV subtypes. Treatment with benzathine penicillin G was successful for both partners. Conclusion: This study emphasizes the need for Couple Consultation during pregnancy to identify and treat possible sexually transmitted infections.